Redox Mechanisms in Regulation of Adipocyte Differentiation: Beyond a General Stress Response - Fan Jiang (Cells, 2012)
In this review, we summarize advances in our understanding of redox-sensitive mechanisms that regulate adipogenesis. Current evidence indicates that reactive oxygen species may act to promote both the initiation of adipocyte lineage commitment of precursor or stem cells, and the terminal differentiation of preadipocytes to mature adipose cells. These can involve redox regulation of pathways mediated by receptor tyrosine kinases, peroxisome proliferator-activated receptor γ (PPARγ), PPARγ coactivator 1α (PGC-1α), AMP-activated protein kinase (AMPK), and CCAAT/enhancer binding protein β (C/EBPβ). However, the precise roles of ROS in adipogenesis in vivo remain controversial. More studies are needed to delineate the roles of reactive oxygen species and redox signaling mechanisms, which could be either positive or negative, in the pathogenesis of obesity and related metabolic disorders.